Experimental and numerical study on thermal management of air-cooled proton exchange membrane fuel cell stack with micro heat pipe arrays. (1st January 2023) - Yang, Mingguang; Quan, Zhenhua; Zhao, Yaohua; Wang, Lincheng; Liu, Zichu; Tang, Sheng
Graphical abstract: Highlight: A fuel cell stack with micro heat pipe arrays is developed and tested. Internal electrochemical parameters within a single cell is analyzed. Using micro-heat pipe arrays increases the load level of the stack. Micro-heat pipe arrays change the temperature distribution for cells. Micro-heat pipe arrays enhance the hydration of the proton exchange membrane. Abstract: In this study, micro-heat pipe arrays (MHPAs) are integrated into air-cooled proton exchange membrane fuel cells (PEMFCs) to enhance their load level and heat dissipation. Experiments are carried out to compare the relevant thermal performance of the stack consisting of 50 units at different operating conditions. A three-dimensional, non-isothermal, and steady-state numerical model of a single cell in the stack is then established to analyze the effect of a MHPA on the electrochemical parameters within the cell. The results of the experiments show that the load level of the stack with MHPAs is 40 % higher than that without MHPAs near the limit temperature. Meanwhile, the average temperature of the stack with MHPAs is 8.3 °C lower than that without MHPAs at 33 A, and MHPAs make the temperature more uniform. Numerical study shows that the decrease of cell temperature by MHPA enables the proton exchange membrane to maintain better hydration and higher current density. At an operating voltage of 0.628 V, the average temperature in the membrane of a single cell with MHPA is 8.8 °C lower than that of PEMFC, and the average water content and current density are 2.01 and 241.06 A/m 2 higher than those without MHPA, respectively.